Quality of Service Support Research for Key Applications in Wireless CDMA Network - Tao Luo; Congjie Mao (Dianxin kexue)
As one of distinctive scenarios, QoS support for key services could make differential protection for self-operated services of China Telecom and other CP／SP services. It could control and schedule users, services and network traffic combined with PCC technology. Key technical and deploy solutions of QoS support for services were analyzed and deeply researched, the reasonable solution uesed for China Telecom CDMA network was given.